Determination and Commitment of Mechanosensory Hair Cells - Matthew W. Kelley (The Scientific World Journal)
Sound and movement are perceived through the vibration of modified ciliary bundles located on the apical surfaces of specialized mechanosensory hair cells. These hair cells derive from specific regions of the otocyst that become determined to develop initially as sensory epithelia and ultimately as either hair cells or supporting cells. The number of hair cells in an individual vertebrate is surprisingly small and the ability to replace these cells varies among different classes. The molecular and cellular factors that specify hair cell identity are not known, but the results of recent experiments have begun to identify some of the signaling pathways that play important roles in hair cell development. This review will describe recent findings related to the factors that influence the final choice of a progenitor cell to develop as a hair cell and discuss their implications for the overall development of the auditory and vestibular systems.